Body self-esteem, physical self-concept, and eating disorders in university students: a cross-sectional study - Edwin Gustavo Estrada-Araoz; Gilber Chura-Quispe; Guido Ayay-Arista; Elizabeth Orfelia Cruz-Laricano; Yasser Malaga-Yllpa; Jimmy Nelson Paricahua-Peralta; Libertad Velasquez-Giersch (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: currently, the university stage represents a period in which students undergo significant personal, social, and emotional transformations. In this context, concerns related to body esteem, physical self-concept, and eating disorders often arise.